Creative Strategy Analysis of SWJ Ambassador Tourism Village Promotion Content (Case Study of Creative Strategy Analysis of Tourism Village Promotion Content by Instagram Account @_nikenaf) - Anisyahrini, Rini; Wardiani, Winne; Illahi, Azizun Kurnia (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
Tourism in West Java is very diverse, ranging from massive tourist destinations and alternative tourism. One form of alternative tourism is a tourist village. The presence of a tourist village is an alternative for people who want to visit the beauty and uniqueness of a particular place. Various kinds of tourist villages in West Java have been widely exposed on social media through various kinds of creative content of ordinary social media users and content creators. The West Java Provincial Government formed a community tasked with reaching out to tourist villages and promoting them through social media, the community was named Smilling West Java Ambassador (SWJ Ambassador). The mechanism carried out by SWJ Ambassadors in carrying out promotional activities for tourist villages in West Java is by creating creative content in the form of videos or photos through each ambassador's Instagram. The conceptual framework used includes Creative Content Promotion Strategy in SOSTAC Analysis, social media, SWJ Ambassador program. This research uses a constructivist paradigm with a case study method on creative content promotion of tourist villages by the Instagram account @aqqiki_. Data collection techniques used in-depth interviews with informants and observation of tourist villages that became objects in the selected content. The results found that SWJ Ambassador @_nikenaf carried out a creative content strategy with the SOSTAC model (Situation, Objective, Strategy, Tactics, Actions, Control) and with limited capabilities and the absence of a creative team, sometimes the results and consistency of making promotional content were less massive.